Improving Students' Vocabulary Using Cartoon For TheFourth Grade Students Of SDN Ngemplak 01 Kartasura In2011/2012 Academic Year - Perwitasa, Intan Aris (2012)
The general objective of this research is to improve the students' vocabulary mastery using cartoon. While the specific objectives of this research are to know whether or not cartoon improve the students' vocabulary, to describe how is the implementation of teaching vocabulary using cartoon, and to identify the strengths and weaknesses of teaching vocabulary using cartoon for the fourth grade students of SDN Ngemplak 01 Kartasura in 2011/2012 Academic Year. In achieving the objectives of this research, the writer uses Classroom Action Research (CAR). There are two cycles in this action research in which each cycle is conducted in two meetings. Each cycle of this action research consists of four steps: planning, acting, observing, and reflecting. he research was held in the fourth grade of SDN Ngemplak 01 Kartasura consisting of 32 students. In analyzing the data, the writer uses qualitative analysis taken from observation, test, interview, and document analysis. The result of research shows that cartoon can improve students' vocabulary. It can be seen from increasing mean score of pre-test and post-test. The pre-test is 61.6 and post-test is 86.9, the improvement got by the students is 25.3. The strengths are the students have high interest, are not easily bored in English class, and easy to be memorized for the students. The weaknesses are the writer must spend her spare time at home to prepare material and design the classroom activity, the writer must print the cartoon, and the writer should use both Indonesia and English language. Thus, it can be said that teaching English vocabulary using cartoon technique is successful to improve the students' vocabulary mastery in SDN Ngemplak 01 Kartasura.